Brief description of Synthetic Biology and the importance of its relationship with other disciplines - Muñoz-Miranda, L. A.; Higuera-Ciapara, I.; Gschaedler-Mathis, A. C.; Rodríguez-Zapata, L. C.; Pereira-Santana, A.; Figueroa Yáñez, L. J. (Revista Mexicana de Ingenieria Biomedica, 2018)
Synthetic biology (SynBio) it is considered a very recent discipline. View as a tool serves to design or re-design biolo-gical systems, giving them improved qualities or new qualities. In the SynBio, the design of new biological systems requires very precise molecular tools, such as: a) bioinformatics, b) sequencing NGS (Next Generation Sequencing), assembly and synthesis of DNA c) and CRISPR-Cas9 genome editing. Within the SynBio there are other social profile disciplines which concerned to ethical, legal, philosophical, and economic, and for that reason it is considered a multidiscipline. The SynBio is promoting the development of new (emerging) technologies based on an engineering perspective. In SynBio, DNA is understood in a practical and abstract way as a series of parts that can be assembled in a certain order to obtain the desired products once the functionality of each part is known. The SynBio has given rise to a new conception of the economy worldwide and consequently the term Bioeconomy is already taken very seriously as a new discipline that will transform societies.